An ecotopian lexicon - Schneider-Mayerson, Matthew; Bellamy, Brent Ryan (University of Minnesota Press, 2019)
"Proceeding from the sense that the dominate western languages do not have the words we need to describe our environmental crisis or propose to it, this book is a collaborative volume of short, accessible chapters that propose ecologically productive terms - drawn from other languages, from speculative fiction, and from activist subcultures - as a means of envisioning and inspiring responses and alternatives to fossil-fueled neoliberal capitalism"--